Reliability analysis of subsea blowout preventers with use of Bayesian networks - Hia, Wei Jie (2015)
Subsea blowout preventers (BOPs) play crucial roles in ensuring a safe drilling condition and failures to these BOPs may cause catastrophic accidents such as the Deepwater Horizon accident. Due to the recent accidents which occurred during the drilling activities, there has been a realisation of the importance of performing reliability analysis for subsea blowout preventer systems to ensure its functionality. Traditional methods previously used for the evaluation like the Fault Tree Analysis were reviewed and subsequently, Bayesian Networks, a technique that was gaining increasing attention but until now still rarely used for the reliability evaluation for BOPs was introduced and applied on different cases, analysing on the various effects and causes leading to the failures, to showcase its ability and advantages.